1992
DOI: 10.1002/jccs.199200042
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of α‐Amino Acids from Glycine

Abstract: Enantioselective synthesis of optically active α‐amino acids from glycine via Schiff base employing (+)‐N,N‐diisopropyl‐10‐camphorsulfonamide as a chiral template is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…(1 S )-1,1-Dimethylethyl 2-( N , N -Bis(1-methylethyl)-7,7-dimethyl-1-methanesulfonamidobicyclo[2.2.1]hept-2-ylidene amino)ethanoate (2). 4a, A mixture of tert -butyl glycinate (157 mg, 1.20 mmol) and thione 3 (331 mg, 1.00 mmol) in toluene (7 mL) was heated under reflux for 24 h. After cooling, the mixture was filtered. The filtrate was concentrated and purified by silica gel column chromatography eluted with ethyl acetate−hexane (1:5) to give Schiff base 2 (417 mg, 98%): mp 68.0−69.5 °C (hexane); [α] 23 D 23.5 ( c 2.00, CHCl 3 ); IR (KBr) 1735, 1684 cm -1 ; 1 H NMR δ 3.94, 3.92 (ABq, J = 16.0 Hz, 2H), 3.77 (septet, J = 6.8 Hz, 2H), 3.70 (d, J = 14.4 Hz, 1H), 2.86 (d, J = 14.4 Hz, 1H), 2.61 (ddd, J = 12.2, 12.0, 4.4 Hz, 1H), 2.27 (ddd, J = 16.8, 3.6, 3.6 Hz, 1H), 1.97−1.87 (m, 2H), 1.79 (d, J = 16.8 Hz, 1H), 1.56−1.54 (m, 1H), 1.43 (s, 9H), 1.31 (d, J = 6.8 Hz, 6H), 1.30 (d, J = 6.8 Hz, 6H), 1.30−1.20 (m, 1H), 1.16 (s, 3H), 0.83 (s, 3H); 13 C NMR δ 183.3, 169.2, 80.7, 55.1, 54.7, 52.8, 48.0, 47.7, 43.8, 34.9, 27.9, 27.2, 27.0, 22.5, 21.9, 20.0, 19.4; HRMS calcd for C 22 H 41 O 4 N 2 S (M + 1), 429.2788, found 429.2796.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…(1 S )-1,1-Dimethylethyl 2-( N , N -Bis(1-methylethyl)-7,7-dimethyl-1-methanesulfonamidobicyclo[2.2.1]hept-2-ylidene amino)ethanoate (2). 4a, A mixture of tert -butyl glycinate (157 mg, 1.20 mmol) and thione 3 (331 mg, 1.00 mmol) in toluene (7 mL) was heated under reflux for 24 h. After cooling, the mixture was filtered. The filtrate was concentrated and purified by silica gel column chromatography eluted with ethyl acetate−hexane (1:5) to give Schiff base 2 (417 mg, 98%): mp 68.0−69.5 °C (hexane); [α] 23 D 23.5 ( c 2.00, CHCl 3 ); IR (KBr) 1735, 1684 cm -1 ; 1 H NMR δ 3.94, 3.92 (ABq, J = 16.0 Hz, 2H), 3.77 (septet, J = 6.8 Hz, 2H), 3.70 (d, J = 14.4 Hz, 1H), 2.86 (d, J = 14.4 Hz, 1H), 2.61 (ddd, J = 12.2, 12.0, 4.4 Hz, 1H), 2.27 (ddd, J = 16.8, 3.6, 3.6 Hz, 1H), 1.97−1.87 (m, 2H), 1.79 (d, J = 16.8 Hz, 1H), 1.56−1.54 (m, 1H), 1.43 (s, 9H), 1.31 (d, J = 6.8 Hz, 6H), 1.30 (d, J = 6.8 Hz, 6H), 1.30−1.20 (m, 1H), 1.16 (s, 3H), 0.83 (s, 3H); 13 C NMR δ 183.3, 169.2, 80.7, 55.1, 54.7, 52.8, 48.0, 47.7, 43.8, 34.9, 27.9, 27.2, 27.0, 22.5, 21.9, 20.0, 19.4; HRMS calcd for C 22 H 41 O 4 N 2 S (M + 1), 429.2788, found 429.2796.…”
Section: Methodsmentioning
confidence: 99%
“…Since the discovery of l -3-(3,4-dihydroxyphenyl)alanine ( l -DOPA) for the treatment of Parkinson's disease, the preparation of this specific compound has attracted considerable synthetic attention . The synthesis of optically active α-amino acids has been intensively investigated in the past couple decades. , We have reported that enantioselective synthesis of α-amino acids from the asymmetric enolate alkylation of Schiff base, derived from the condensation of tert -butyl glycinate with N-substituted or N,N-disubstituted (1 S )-(+)-10-camphorsulfonamides, could be achieved in high ee . Here, we report an enantioselective synthesis of d -DOPA with high ee employing this method.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have suggested that this species is a potential source of bioactive antimicrobial agents and could be used as a natural preservative and for nutraceutical formulations (Gupta et al, 2011a). The leaves and seeds has a higher total phenolic content, comparing to other sea buckthorn species (Lu, 1992), as well leaves showed antiinflammatory properties (Padwad et al, 2006). During the last year, extracts from this plant were used in the USA as an food supplement (Saikia and Handique, 2012).…”
Section: Introductionmentioning
confidence: 99%